2014
DOI: 10.3402/ijch.v73.21310
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic difference in the prevalence of angina pectoris in Sami and non-Sami populations: the SAMINOR study

Abstract: ObjectiveTo assess the population burden of angina pectoris symptoms (APS), self-reported angina and a combination of these, and explore potential ethnic disparity in their patterns. If differences in APS were found between Sami and non-Sami populations, we aimed at evaluating the role of established cardiovascular risk factors as mediating factors.DesignCross-sectional population-based study.MethodsA health survey was conducted in 2003–2004 in areas with Sami and non-Sami populations (SAMINOR). The response r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
16
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 37 publications
1
16
1
Order By: Relevance
“…In the latter study, stomach pain was associated with milk intake. Also, our finding of higher prevalence of chest pain is in accordance with a study based on SAMINOR data, which reported a higher prevalence of angina pectoris among the Sami compared to the non-Sami (36). Furthermore, interpersonal violence has been associated with pain in the stomach and pelvic in several other studies.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the latter study, stomach pain was associated with milk intake. Also, our finding of higher prevalence of chest pain is in accordance with a study based on SAMINOR data, which reported a higher prevalence of angina pectoris among the Sami compared to the non-Sami (36). Furthermore, interpersonal violence has been associated with pain in the stomach and pelvic in several other studies.…”
Section: Discussionsupporting
confidence: 93%
“…Other studies among Sami in Finland and Russia confirm the higher prevalence of lactose intolerance compared to the majority populations (34,35). Moreover, a study based on SAMINOR data reported a higher prevalence of angina pectoris (heart cramp) among the Sami compared to the non-Sami (36). …”
mentioning
confidence: 99%
“…The authors suggest exposure to chronic stress as a result of marginalisation as a plausible explanation. No gender differences were found [26]. The prevalence of selfreported myocardial infarction was similar for Sami and non-Sami people in rural areas of Norway, based on a health survey in 2003-2004.…”
Section: Cardiovascular and Cerebrovascular Diseasesmentioning
confidence: 80%
“…There is also evidence from Norway that self-reported myocardial infarction rates were similar among Sami and non-Sami, but Angina pectoris was more prevalent among Sami. In Sweden, cardiovascular disease rates were similar between Sami and non-Sami [25][26][27][28][29]. As with the general populations of the Nordic countries, the incidence of cancer among the Sami people has increased over recent decades.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation